(untitled) - RETNO SULISTYOWATI, NOFI (Language Horizon: Journal of Language Studies, 2015)
Abstract In conversations the language of lesbians can be seen through the study of language and gender. Examining the language of lesbians and gay men is critical to the study of language and gender, the relationship between language and gender mixed-sex conversations have continued to be discussed based on data from heterosexual or presumed heterosexual speakers. This study focuses on how the linguistic strategies run within the lesbian characters in the movie correlating to the purpose of showing both dominance and solidarity in conversation. The purpose of this study is to analyze the utterances of lesbian characters containing linguistic strategy. The description consists of (1) what linguistic strategies do lesbian use with their partner in the movie Reaching for the Moon; (2) how are the reasons using of those linguistic strategies used by lesbian in the movie Reaching for the Moon; (3) how are the effects of using linguistics strategies by lesbian in the movie Reaching for the Moon to the interlocutors. The researcher used descriptive qualitative method using the main theory of Johnson and Christersen (2012) linguistis strategy theory by Tannen (1994). The data analysis requires the process of (1) ordering the data based on each sub sections linguistic strategy and (2) discussing the function of using those kind linguistic strategy and the effect to interlocutors.The result shows that this study has found some linguistic strategies used by lesbians in the movie. They are interruption, indirectness, topic rising, silence and adversativeness. However, the linguistic strategy minimal response does not appear in this movie. Each of the strategies has their own function and effect to interlocutor depending on the context in conversations. Some strategies are used to create domination to the interlocutor while the other are used as a defensive strategy to create solidarity and closeness to the interlocutor. The one that create domination is Lota who dominates Elizabeth.In conclusion, linguistic strategy uttered by lesbian characters in the movie “Reaching for the Moon” leads a purpose to both creating domination by gaining the conversation floor and showing solidarity as a sign of powerless person. Key words:linguistic strategy, lesbian, conversation, power, domination, powerless